Styl a téma. O jednom aspektu pojetí stylu v díle Karla Hausenblase - Petr Mareš (Acta Universitatis Carolinae: Philologica)
Karel Hausenblas defined style as a principle of integration that goes through all levels of the text (from language to theme) and forms it to a unified whole. The paper focuses on the position of the thematic level of the text in this conception. First theoretical arguments for the inclusion of theme into the sphere of style are discussed, and then the evolution of Hausenblas’s views is summarized. According to Hausenblas, the stylistic integration of the linguistic and thematic levels of text is accomplished by repetition of equivalent means and by synergy of various stylistic features. He tried to demonstrate the ways of this integration in his thorough analyses of Czech prosaic works. Further, Hausenblas stated that the style is based on two operations, the selection from a repertoire of elements and the composition of selected items. The homogenous character of style is so declared, but the possibilities and ways of selection from a repertoire differ in relation to language and in relation to thematic units.